2007
DOI: 10.1016/j.pbiomolbio.2007.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of connexins with other membrane channels and transporters

Abstract: Cell-to-cell communication through gap junctions exists in most animal cells and is essential for many important biological processes including rapid transmission of electric signals to coordinate contraction of cardiac and smooth muscle, the intercellular propagation of Ca 2+ waves and synchronization of physiological processes between adjacent cells within a tissue. Recent studies have shown that connexins can have either direct or indirect interactions with other plasma membrane ion channels or membrane tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 82 publications
1
35
0
Order By: Relevance
“…Previous studies also demonstrated the functional interplay between Cx43/ Cx45 with other ABC transporters, namely with cystic fibrosis transmembrane conductance regulator (CFTR). Indeed, it was shown that GJIC can be regulated by CFTR through modulation of voltage sensitivity and gating of Cx channels (47). Although the molecular mechanisms involved are still unclear, it is known that CFTR/GJ crosstalk relies on a complex signaling network, involving c-src.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also demonstrated the functional interplay between Cx43/ Cx45 with other ABC transporters, namely with cystic fibrosis transmembrane conductance regulator (CFTR). Indeed, it was shown that GJIC can be regulated by CFTR through modulation of voltage sensitivity and gating of Cx channels (47). Although the molecular mechanisms involved are still unclear, it is known that CFTR/GJ crosstalk relies on a complex signaling network, involving c-src.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the inhibition of CFTR by ATP depletion abolished GJIC, whereas the activation of CFTR by cAMP opened gap junction channels within minutes (37,38). Therefore, a reciprocal regulation of the activity of the two channels occurs, and interestingly, the gating of gap junctions is impaired in CF epithelial cells (21). Regarding the importance of gap junctions in integrating multiple signaling pathways for the regulation of ASL volume, and thus the maintenance of a proper epithelial host defense, the altered regulation of GJIC may represent an additional layer of dysfunction in airway diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, gap junctions may contribute to the coordination of intercellular signaling, because they provide direct aqueous pores between neighboring cells, thus allowing the intercellular spread of ions, nucleotides, and second messengers (20). Gap junctions are present in airway epithelial cells, and the regulation of their channel activity is defective in CF (21,22). Thus, this study set out to determine whether gap junctions mediate the GPCR-induced activation of CFTR, and if their blockade could inhibit ASL volume homeostasis.…”
Section: Clinical Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…The interaction of Cx43 with other proteins is gaining considerable importance for their role in the regulation of Cx43 trafficking, assembly and disassembly as well as the dynamic modulation of channel opening (Chanson et al, 2007;Hervé et al, 2007). Although, 14-3-3 has been shown to interact with several integrins including b1, aLb2 and a4 (Deakin et al, 2009;Han et al, 2001;Nurmi et al, 2006), our study is the first to show that 14-3-3h interacts with integrin a5.…”
Section: Discussionmentioning
confidence: 62%